THE EFFECTIVENESS OF DIGITAL MARKETING THROUGH TIKTOK ON RETURN ON INVESMENT (ROI) OF MICRO SMALL, AND MEDIUM ENTERPRISES IN KONAWE REGENCY - Muhamad Pariama; Surifan Laembo (RADJA PUBLIKA, 2025)
Digital transformation has opened up many opportunities for micro, small, and medium enterprises (MSMEs) to market their products more widely and effectively. One platform experiencing rapid growth and holding significant potential for digital marketing strategies is TikTok. In Konawe Regency, several MSMEs have begun using this platform, but little research has been conducted on its effectiveness in increasing Return on Investment (ROI). The purpose of this study is to determine the impact of digital marketing campaigns using TikTok on the ROI of small and medium enterprises (MSMEs) in Konawe Regency. In this study, engagement, content reach, and sales conversion metrics were the most important indicators of effectiveness. It is hoped that the results will provide a more accurate understanding of how social media helps small businesses grow economically. This research was conducted quantitatively using survey methods, descriptive analysis, and simple linear regression. The analysis was conducted to determine the relationship between the intensity of TikTok use as a promotional medium and increased business ROI. Data was collected through questionnaires and interviews with MSMEs who actively use TikTok as a promotional medium. The results of this study can be used as a reference in formulating policies aimed at increasing the competitiveness of digital-based MSMEs, especially by optimizing the TikTok platform.